42. ADAPTING TO THE LEARNING ENVIRONMENT OF STUDENTS OF HOA BINH COLLEGE OF TECHNICAL AND TECHNOLOGY HOA BINH PROVINCE IN 2023-2024 (Vietnam Journal of Community Medicine, 2024)
Objective: Describe the learning adaptation of students at Hoa Binh College of Technical and Technology in the 2023-2024 school year.Research method: Using a cross-sectional descriptive research design combining qualitative and quantitative methods with 200 students answering the questionnaire.Results: The learning adaptation of students at Hoa Binh College of Technical and Technology was assessed on 4 skills including the ability to identify problems, the ability to solve problems, the ability to find solutions and the ability to sharing and cooperation skills. The results show average score of the ability to identify problems is highest (3.49 points), second is the ability to solve problems (3.41 points), followed by the ability to find solutions (3.29 points) and finally the ability to cooperate and share (3.26 points).Conclusion: Research shows that students' adaptation to the learning environment is expressed through 4 abilities. In general, students have a fair level of adaptation to the learning environment in terms of problem identification and problem solving ability, students are only at a normal level in adapting to the learning environment in terms of the ability to find solutions and the ability to cooperate and share.
Keywords: Adapting the learning environment; identifying problems; finding solutions, solving problems; sharing and collaborating; Hoa Binh College of Technical and Technology.